Epizoozoan Trepostome Bryozoans on Nautiloids from the Upper Ordovician (Katian) of the Cincinnati Arch Region, U.S.A.: An Assessment of Growth, form, and Water Flow Dynamics. (May 2014) - Wyse Jackson, Patrick N.; Key, Marcus M.; Coakley, Stephen P.
Abstract : Spatiopora Ulrich, 1882 is a trepostome bryozoan that is found encrusting living orthoconic nautiloids in the Upper Ordovician (Katian) of North America, as do several other bryozoans. These epizoozoan bryozoans are characterized by possessing thin unilaminate zoaria with rows of elongate maculae, which may be monticulate and aligned coaxially to the host growth axis. These develop a distinctive linear shape in response to growing on a conical host, rather than as a response to channelized water flow along the host. Monticules increase in size and spacing adorally until a maximum inter-macular area is reached that results in a decline in surface water flow efficiency, and a new monticular line is inserted. Orthocones normally swam forward at lower velocities that enabled lophophore eversion and feeding, which would have been impossible at the higher speeds reached when the host jetted backwards during escape. Monticules reduced drag and turbulence acting on the orthocones which allowed for more efficient venting of bryozoan macular excurrents. Characteristic elliptical monticule growth continued even after death of the motile host. A Trypanites -bryozoan-orthoconic nautiloid association shows a complex biological and taphonomic relationship between these organisms.